Students’ Perception towards English Learning Material during Full Online Learning at SMAN 5 Padang - Feggy Nisa Sabelina; Yuli Tiarina (Journal of English Language Teaching, 2021)
The learning process is transitioning to distance learning due to the pandemic. Along with online learning practices, teachers make online learning to support the teaching and learning process, such as providing learning materials and delivering learning materials using technology. This study aims to explore students' perceptions of English learning material during full online learning. The sample in this study was taken randomly with 135 students of SMA N 5 Padang, consisting of class 12 MIPA 1-7 and class 12 IPS 1-5. They were given 25 questions to explore their perceptions about English learning material during online learning. Quantitative descriptive is used in this research. The results showed that the students were neutral towards the learning material and the delivery of the material used during online learning. This was indicated by an average score of 2.83. However, they argue that the material used in online classes is more difficult than the material used in face-to-face learning. This makes students cannot decide their perceptions of learning material and delivery of material during online learning.